Dividend Policy Mediates the Effect of Financial Performance on Firm Value - Zessicha Belliana Putri; Khuzaini Khuzaini; Suhermin Suhermin (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
This study aimed to examine the effect of financial performance on firm value, with dividend policy as an intervening variable (A Study at Manufacturing Companies in Indonesia Stock Exchange). The population was manufacturing companies listed on Indonesia Stock Exchange from 2016-up to 2020. Furthermore, the data collection technique used purposive sampling with 72 companies as the sample. The data used were secondary, in companies’ annual reports. The data analysis technique used SEM-PLS with Smart PLS 3.0. The analysis result from measurement models (outer model) through internal consistency test, convergent and discriminant validity showed that all variables had fulfilled the testing requirements. Based on the model structure (inner model), path coefficient analysis with bootstrapping and determinant coefficient test was used to perceive either relation or ability of exogenous variables in describing endogen variables. In addition, the hypothesis test concluded that liquidity, leverage, activities, and profitability had a significantly positive effect on dividend policy. In contrast, liquidity and activities had a positive but insignificant effect on firm value. On the other hand, leverage, profitability, and dividend policy significantly positively impacted firm value. In brief, dividend policy could not mediate the effect of liquidity and leverage on firm value, yet it could judge the impact of activities and profitability on firm value.